Data Hiding using difference between adjacent pixels and bit plane swapping (International Journal of Engineering and Computer Science, 2014)
In this paper, we have implemented a novel technique for hiding text messages in a gray scale image. This technique involves data hiding using cryptography and steganography, which makes it a strong data hiding mechanism. In this method, we first apply cryptography to secret message and then hide it inside a gray scale image using steganography